Perppu Pengawasan Hakim Mk Versus Putusan Final Mk - Malik, Malik (Jurnal Konstitusi, 2013)
Government Regulation in Lieu of Law (Perppu) No. 1 of 2013 about the Second Amendment to Act No. 24 of 2003 about Constitutional Court (MK) is an appropriate step to recover public trust to MK after the arrest of non-active Head of MK Akil Mochtar by Corruption Eradication Commission (KPK). Many crucial things are found  in Perppu No.1 of 2013 about MK and these are considered as the problem roots   but also the efficacious herbs to deter against the replicated corruption practice at MK. One of them is the supervision system of Constitutional Justices. Justices of  MK have been once becoming the object of the supervision of Judicial Commission (KY), but the release of the Verdict of Constitutional Court No. 005/PUU-IV/2006  has made the authority of KY to supervise Constitutional Justices degraded into inconstitutional. The verdict of Constitutional Court is final and binding, but it cannot still escape from erga omnes principle, meaning that the verdict is binding  in general term and also binding for the object of dispute.